2020
DOI: 10.1021/acsami.0c13707
|View full text |Cite
|
Sign up to set email alerts
|

Conformal Coating of Orthopedic Plates with X-ray Scintillators and pH Indicators for X-ray Excited Luminescence Chemical Imaging through Tissue

Abstract: We describe a material that allows for high spatial resolution pH mapping through tissue using X-ray excited luminescence chemical imaging (XELCI). This is especially useful for detecting implant associated infection and elucidating how the local biochemical environment changes during infection and treatment. To acquire one pixel in the image, a focused X-ray beam irradiates a small region of scintillators coated on the implant and the X-ray excited optical luminescence spectrum is modulated by indicator dyes … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Previous studies have shown that the point spread function is about 20 mm for 650–800 nm light through 10 mm of tissue (in slab geometry). [ 46 ] The intensity profile of vertical lines through the center of each image demonstrates the signal decrease and spread for the drug release region (left‐most peak) and constant drug reference region (right‐most peak) (Figure 3E). The full‐width half‐maximum(FWHM) for the signal through 5 and 10 mm of tissue, calculated after four iterations of Gaussian smoothing (Figure S3, Supporting Information) to reduce image noise, is 13.1 and 16.5 mm, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that the point spread function is about 20 mm for 650–800 nm light through 10 mm of tissue (in slab geometry). [ 46 ] The intensity profile of vertical lines through the center of each image demonstrates the signal decrease and spread for the drug release region (left‐most peak) and constant drug reference region (right‐most peak) (Figure 3E). The full‐width half‐maximum(FWHM) for the signal through 5 and 10 mm of tissue, calculated after four iterations of Gaussian smoothing (Figure S3, Supporting Information) to reduce image noise, is 13.1 and 16.5 mm, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…X-ray excited luminescent chemical imaging (XELCI) is a novel medical imaging technique used to non-invasively detect and monitor bacterial biofilm on implant surfaces ( Wang et al, 2015 ; Uzair et al, 2020 ). In the XELCI technique, a combination of X-ray excitation to provide high-resolution images and optical detection of infection is used.…”
Section: Bacterial Infection Diagnosismentioning
confidence: 99%
“…The light that passes through tissue is then collected, and the spectral ratio is measured to determine the pH. A focused X-ray beam irradiates a point in the scintillator film, and a pH image is formed point-by-point by scanning the beam across the sample ( Uzair et al, 2020 ). A pH sensor film was developed by Wang et al and can be coated on implant surfaces to noninvasively map pH ex vivo in porcine tissue using XELCI ( Wang et al, 2015 ).…”
Section: Bacterial Infection Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we have shown that we can image through 6 mm of chicken breast. We do not know the maximum but would expect around 2 cm should be feasible because we are able to acquire focused X-ray luminescence images through around 2 cm of tissue and bone in an ex vivo rabbit model [42], and we typically observe much higher signals from upconversion luminescence than for X-ray luminescence [43]. However, deeper tissue imaging may require better optical collection efficiency, larger or brighter sensors, longer acquisition times, and/or higher noise levels because the excitation and emission light are exponentially attenuated by tissue.…”
Section: Small Signal Analysismentioning
confidence: 99%